Triglycerides/high-density lipoprotein-cholesterol ratio outperforms traditional lipid indicators in predicting metabolic dysfunction-associated steatotic liver disease among U.S. adults - Yuan, Jin; He, Xuequan; Lu, Yan; Pu, Xuehua; Liu, Lihe; Zhang, Xuejun; Liao, Jinping; Li, Guiling; Luo, Ying; Zhang, Tianwu (Frontiers in Endocrinology, 2025)
ObjectiveTriglycerides (TG), high-density lipoprotein cholesterol (HDL-c), and their ratio (TG/HDL-c) are key lipid markers associated with metabolic dysfunction. This study aims to investigate the association of TG, HDL-c, and TG/HDL-c ratio with metabolic dysfunction-associated steatotic liver disease (MASLD) and to assess whether TG/HDL-c ratio provides superior predictive ability for MASLD compared to TG or HDL-c alone.ImportanceAlthough previous research has explored the relationship between TG/HDL-c and MASLD, the applicability of these findings across different ethnicities and populations remains uncertain. Additionally, this study is based on NHANES data, which relies on self-reported measures and lacks longitudinal follow-up, limiting the ability to establish causal relationships. While we adjusted for multiple covariates, residual confounding cannot be ruled out. Therefore, further large-scale, prospective studies are needed to validate these associations and assess the long-term predictive value of TG/HDL-c ratio for MASLD.MethodsA cross-sectional study utilizing the NHANES 2017-2020 database was conducted. We performed univariate and multivariate logistic regression analyses to examine the associations between TG, HDL-c, and the TG/HDL-c ratio with MASLD. Receiver Operating Characteristic (ROC) curve analysis was used to evaluate the predictive effectiveness. Sensitivity analysis was carried out using multiple imputation for missing data and subgroup stratification to validate the findings.ResultsTG, HDL-c, and TG/HDL-c ratio were significantly associated with MASLD (p < 0.05 for all). The TG/HDL-c ratio demonstrated the highest predictive value (AUC = 0.732, 95% CI: 0.683–0.781), compared to TG (AUC = 0.713, 95% CI: 0.664–0.762) and HDL-c (AUC = 0.313, 95% CI: 0.264–0.362). The weak predictive power of HDL-c alone may be attributed to its complex role in lipid metabolism and potential confounding by other metabolic factors.ConclusionMaintaining favorable levels of TG, HDL-c and TG/HDL-c ratio may lower MASLD risk. Using TG/HDL-c ratio could improve prediction models compared to individual TG or HDL-c markers.